PERENCANAAN STRUKTUR ATAS BANGUNAN MASJID DI MAGETAN - Hendy Wijaya; Aurelia Clarissa; Emillio Chandra; Alfred Jonathan Susilo (PROSIDING SERINA, 2021)
Design of a mosque building requires the presence of experts in the field of Civil Engineering in assisting the process of designing the structure of the building. This activity describes the author's contribution as a Civil Engineering expert in helping to plan the structure of the mosque building in Desa Buluharjo, Kecamatan Plaosan, Kabupaten Magetan, Jawa Timur. The building is a one-story building with an area of ±545 m2. The implementation of this activity begins with conducting a site survey through photos and video recordings sent by Mitra PKM. This was done because this activity was carried out during the Covid-19 pandemic. After studying the land situation, coordination with the architect was carried out to discuss the design of the mosque. Furthermore, the analysis and design of the building structure is carried out from the agreed architectural design concept. The results of the structural design are outlined in the form of drawings which are then submitted to the Mitra PKM as the final product of the PKM activities and used as one of the reference drawings for the building construction. This building is designed using reinforced concrete with concrete grade of fc '25 MPa. The structural system is a special moment resisting frame. The design of the concrete structures refer to SNI 2847-2019. The building importance factor is 1.50 in accordance with the provisions of SNI 1726-2019 for the building risk category IV.